A novel sunflower broomrape race with unusual virulence potentially caused by a mutation - Fernández-Melero, Belén; Martín-Sanz, Alberto; del Moral, Lidia; Pérez-Vich, Begoña; Velasco, Leonardo (Frontiers in Plant Science, 2023)
The sunflower broomrape (Orobanche cumana Wallr.) gene pools of the Guadalquivir Valley and Cuenca province in Spain had predominantly race-F virulence. A new race G was observed recently in the Guadalquivir Valley potentially due to the genetic recombination of the avirulence genes of both gene pools. In this research, we have studied populations with atypical virulence from Cuenca. These populations parasitize on DEB2 sunflower line, resistant to all race-G populations evaluated. Ten populations collected in Cuenca province were evaluated with sunflower differential lines and genotyped with 67 SNP markers. Although genetic recombination with individuals of the Guadalquivir Valley gene pool has been observed in most populations, recombination of avirulence genes was discarded as the cause of the new virulence because the population with the highest degree of attack on DEB2 showed no introgression from an external gene pool. Accordingly, a point mutation is proposed as the putative cause of the new virulence. The present study provided a detailed characterization of each population, including the accurate classification of the individuals belonging to each of the classical Spanish gene pools, F1 hybrids, and those that evolved from hybridization between both gene pools. This information is essential to understand how sunflower broomrape populations are evolving in Spain, which in turn may be helpful to understand the dynamics of sunflower broomrape populations in other areas of the world and use this information to develop durable strategies for resistance breeding.